Farmers' heterogeneous motives, voluntary vaccination and disease spread: an agent-based model. (5th December 2019) - Sok, Jaap; Fischer, Egil A J
Abstract: Animal health authorities responsible for effective voluntary livestock disease control need to consider the dynamic interplay between farmers' collective behaviour and disease epidemiology. We present an agent-based model to simulate vaccination scheme designs that differ in expected adverse vaccine effects, communication strategies and subsidy levels. Specific scheme designs improve the vaccine uptake by farmers at the start of a livestock disease epidemic compared with a base scheme of minimal communication and subsidy. The results suggest that motivational mechanisms activated by a well-designed risk communication strategy are equally or more effective in increasing vaccination uptake than providing more financial compensation.